If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6N + -1N = 14 Combine like terms: -6N + -1N = -7N -7N = 14 Solving -7N = 14 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Divide each side by '-7'. N = -2 Simplifying N = -2
| -8=-2P+6P | | K+3+6=11 | | 0=X-4-5X | | 2x+3+4x+1= | | -3N+3-6N=3 | | -4V-3V=-14 | | x(n-3)=4 | | 1+-.5= | | 1+.5x= | | 18x^2-27=35 | | 1.5(x+1)+3.5(x+1)=7.5 | | x^2+5x-10=-3x+10 | | 6x^2+2x-15=34-33x | | 28=4/7w | | 1/2w+3/4w | | 2-2=9x+2x | | 2e^4x-3=5 | | Ln(x)+ln(6)=2 | | 6=8s-3/4-20 | | -1+a/5=-4 | | 6x^2-2x+4=24 | | 8m+3=5m+18 | | x+(x*0.0975)=25 | | x^2-7x+4=-6 | | (-50)x(-4)= | | 5x^2+7x-16=32-27x | | (-8)x(-2)= | | 1200=3x+y | | 25x+70= | | 4=6(x-5)+2-5x | | -0.25+0.75= | | 1/3x+7/6x=220 |